2008
DOI: 10.1167/iovs.07-0827
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigation of Off-Flap Epi-LASIK for Moderate to High Myopia

Abstract: In comparison with on-flap epi-LASIK, off-flap epi-LASIK offers comparable postoperative pain, a lower level of haze formation, a rapider visual recovery, and better visual quality. Further investigations of a larger number of subjects and longer follow-up periods are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 18 publications
5
40
2
Order By: Relevance
“…The authors did not find any significant difference in postoperative pain intensity between the two groups. The study by Wang et al 13 and our study both indicate the lack of any significant benefit of retaining the epithelial flap after Epi-LASIK.…”
Section: Discussioncontrasting
confidence: 49%
“…The authors did not find any significant difference in postoperative pain intensity between the two groups. The study by Wang et al 13 and our study both indicate the lack of any significant benefit of retaining the epithelial flap after Epi-LASIK.…”
Section: Discussioncontrasting
confidence: 49%
“…The most important initial event after surface ablation is re-epithelialization because the outcome of surface ablation is closely related to epithelial wound healing response [3,19]. Katsanevaki et al [21] and Dai et al [22] reported mean times to epithelial healing after epi-LASIK surgery of 4.7 ± 0.87 and 3.80 ± 0.59 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [19] reported that off-flap epi-LASIK offers comparable postoperative pain, a lower level of corneal haze, faster visual recovery, and better visual quality in comparison with on-flap epi-LASIK. Kalyvianaki et al [20] reported that epi-LASIK and off-flap epi-LASIK had equal visual and refractive results for the treatment of low and moderate myopia.…”
Section: Introductionmentioning
confidence: 99%
“…Six RCTs and 3 comparative studies published between 2008 and 2011 met the inclusion criteria [7,8,9,13,14,15,16,17,18]. A total of 489 patients (958 eyes) underwent off-flap epi-LASIK and on-flap epi-LASIK.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some prospective randomized controlled trials (RCTs) have shown that epi-LASIK without retained epithelial flaps (off-flap) had comparable or even better results in regard to postoperative pain, epithelial healing, or vision recovery [7,8,9]. However, the conclusion of a single RCT is limited by the small size, different population, follow-up period, and surgery technique.…”
Section: Introductionmentioning
confidence: 99%